Chronic thromboembolic pulmonary hypertension: a review of risk factors, management and current challenges. (2nd January 2022) - Cannon, John E; Jenkins, David P; Hoole, Stephen P
ABSTRACT: Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is an under-diagnosed complication of acute pulmonary embolism (PE), whereby there is incomplete resolution of pulmonary emboli, which then become organized into obstructive fibrotic material with an associated small vessel vasculopathy. CTEPH is diagnosed by abnormal lung perfusion despite 3-months of oral anticoagulation with persistent pulmonary artery thromboembolic/ fibrotic material confirmed on cross sectional imaging and pulmonary hypertension on right heart catheterization. Without treatment the prognosis is bleak, but there are now three treatment modalities that are effective in treating patients with CTEPH: pulmonary endarterectomy (PEA) surgery, balloon pulmonary angioplasty (BPA) and medical therapy. Areas Covered: We provide a comprehensive review of the literature with particular emphasis on the epidemiology, pathophysiology, diagnosis, and the established and emerging treatments of CTEPH. Expert opinion: It is important to recognize that CTEPH is complication of an acute PE as there are effective and sometimes curative treatments available. In European and North American practice, PEA surgery remains the cornerstone of therapy in patients with CTEPH and accessible disease without significant comorbidity. For those patients with a disease burden that is inaccessible or fails to justify the risk of major surgery, initiating medical therapy and considering BPA is appropriate. Those with persistent pulmonary hypertension after PEA should also receive medical therapy and be considered for BPA or re-do endarterectomy. The available therapies are not necessarily mutually exclusive, and the treatment decision is often subjective and individualized, based on the local available expertise. Further research is needed to understand the optimal treatment strategy for patients and in particular to identify 'responders' and assess the synergies between these three treatment strategies.